Estudo do potencial eletrostático e da termodinâmica de agregação de surfactantes por simulações de dinâmica molecular - Bernardino, Kalil (2018)
Due to the amphiphilic character, the surfactants tend to be adsorbed at the water surface and, in concentrations larger than the critical micellar concentration, they self-assembling in solution with the purpose to reduce the exposed area of the hydrophobic portion to the water. The aggregation thermodynamics of two ionic surfactants (SDS and DTAC) into micelles was studied by means of extensive umbrella sampling simulations with classical force fields and the potential of mean force for the dissociation coordinate was obtained. This methodology was efficient for SDS, which forms more stable micelles, on the other hand, some problems happens for DTAC due to spontaneous dissociations yield inaccuracies in the calculation of the cluster’s center of mass. The potential of mean force obtained for SDS was decomposed by means of the explicit calculation of several enthalpic and entropic components, throughout the dissociation coordinate, in order to explain the driving forces that result in the aggregation free energy. The expansion entropy is given by an analytical expression while the components associated with the orientation of the surfactant in relation to micelle center of mass and the entropy of torsion of dihedrals were calculated by means of probability distributions. Enthalpy and all those entropic components were found to be unfavorable to the aggregation and the driving force for the micelle formation is due to the so-called hydrophobic effect, for the analysis of which a new methodology is proposed, where its contribution is calculated through the entropy variation of the hydrogen bonds in the first two solvation shells of the surfactant in comparison to the same in pure water. In order to obtain the contribution of the hydrophobic effect, was defined the number of variables needed to fully specify a water dimer close to a reference site of the solute and the probability distribution was calculated for each one of those variables in both the simulation with the surfactant and in a referential in pure water to determine the entropy variation per hydrogen bond. The product of the entropy variation per bond by the average number of hydrogen bonds in the first two solvation layers of the solute in each point of the reaction coordinate results in its contribution for the potential of mean force. The entropies were calculated considering both the variables as independent as well as introducing correlation effects between them, in the first case the entropy changes were overestimated while in the second one a good agreement was obtained with the aggregation free energy after adding the rest of calculated components. This methodology allows not only to confirm the hypotheses commonly accepted for hydrophobic solvation, but also to explain, at the molecular level, how the reorganization of water take place near the hydrophobic solute and quantifies its contribution to the energy free of aggregation. The electrostatic potential of the SDS micelle in the presence of both saturated and unsaturated interfaces of the same surfactant were calculated also and was observed that the adsorption of the counter-ions depends on the interface geometry, being more favorable at the flat interfaces due to the greater facility to establish ionic bridges.